Genetic Diversity, Biochemical Properties, and Detection Methods of Minor Carbapenemases in Enterobacterales - Bonnin, Rémy A.; Jousset, Agnès B.; Emeraud, Cécile; Oueslati, Saoussen; Dortet, Laurent; Naas, Thierry (Frontiers in Medicine, 2021)
Gram-negative bacteria, especially Enterobacterales, have emerged as major players in antimicrobial resistance worldwide. Resistance may affect all major classes of anti-gram-negative agents, becoming multidrug resistant or even pan-drug resistant. Currently, β-lactamase-mediated resistance does not spare even the most powerful β-lactams (carbapenems), whose activity is challenged by carbapenemases. The dissemination of carbapenemases-encoding genes among Enterobacterales is a matter of concern, given the importance of carbapenems to treat nosocomial infections. Based on their amino acid sequences, carbapenemases are grouped into three major classes. Classes A and D use an active-site serine to catalyze hydrolysis, while class B (MBLs) require one or two zinc ions for their activity. The most important and clinically relevant carbapenemases are KPC, IMP/VIM/NDM and OXA-48. However, several carbapenemases belonging to the different classes are less frequently detected. They correspond to Class A (SME-, Nmc-A/IMI-, SFC-, GES-, BIC-like…), to class B (GIM, TMB, LMB…), class C (CMY-10 and ACT-28) and to class D (OXA-372). This review will address the genetic diversity, biochemical properties and detection methods of minor acquired carbapenemases in Enterobacterales.